The Effect of Marketing Mix on the Decision to Choose a Private University in Bandung City - Ezra Karamang; Agus Aribowo; Hendry Suhardiman (Dinasti Publisher, 2024)
This study identifies the elements in the marketing mix that influence students' decisions when choosing a private university in Bandung, including product, price, location, promotion, people, building, and process. By understanding the influence of each of these elements, private universities in Bandung are expected to be more effective in attracting students. The research was conducted by applying quantitative methods with verification analysis. Primary data in the study was obtained through distributing questionnaires to 162 students taken from several private universities in Bandung. While secondary data comes from books, previous articles, the internet and other related literature that has been previously examined and analyzed by researchers. Sampling was carried out using non-probability techniques, namely the random sampling method without certain criteria. Findings Individual significance analysis shows that the variables of promotion, people, and process have a significance value below 0.05, while product, price, and place are not individually significant. However, simultaneously, all of these variables have a significant effect on students' decisions to choose private universities in Bandung City.